Adiposidad visceral y su asociación con lípidos séricos e insulinemis en adolescentes obesas - Neri,Daniela (Sociedad Médica de Santiago, 2007)
Background: Increased visceral or abdominal adipose tissue in children and adults is strongly associated with metabolic and a variety of chronic diseases. Aim: To study the association between visceral or external body measurements of adiposity with blood lipids, glucose and insulin levels, in obese female adolescents. Material and methods: In a cross-sectional study, 47 obese female adolescents (body mass index (BMI) >95th percentile) aged 10 to 15 years, were analyzed. Weight, height, BMI, Tanner pubertal stages, skinfold thickness, waist circumference, waist-to-hip ratio, fasting and 120 min post prandial blood glucose, serum insulin, and lipid profile were studied. Visceral fat was assessed by computed tomography at the L4-L5 level, measuring the fat area or the length of a straight drawn line between the spine and the internal border of the rectus abdominus muscle. Results: No association between lipid profile and BMI or external body measurements (skinfold thickness, waist circumference, waist-to-hip ratio) was observed. Total serum cholesterol >170 mg/dL was positively associated with the straight line over 63 mm (a cut-off obtained by ROC analysis (RR 2.64; 1.15-6.08). This association was statistically significant in girls in Tanner I + II (n =21; Fisher, p <0.023), but not with Tanner III + IV (n =26) stages. Increased cholesterol (>170 mg/dL) was also positively associated with a serum insulin >17 uU/mL in the Tanner I + II group (Fisher p<0.05), but not with the homeostasis model assessment of insulin resistance (HOMA). Conclusions: No external body measurement of adiposity was associated to increased serum cholesterol in these obese female adolescents. Increased total cholesterol (>170 mg/dL) was associated with visceral fat (evaluated through the straight line spina-rectus abdominus muscle), and also with a serum insulin >17 uU/ml in those teenagers with Tanner I or II pubertal stages